Irregular HF radio propagation on a subauroral path during magnetospheric substorms - D. V. Blagoveshchensky; T. D. Borisova; J. W. MacDougall (Annales Geophysicae, 2006)
The impact of the main ionospheric trough, sporadic structures, gradients and inhomogeneities of the subpolar ionosphere during substorms on the signal amplitude, azimuthal angles of arrival, and propagation modes for the radio path Ottawa (Canada)-St. Petersburg (Russia) was considered. This subauroral path with the length of about 6600 km has approximately an east-west orientation. The main goals are to carry out numerical modeling of radio propagation for the path and to compare the model calculations with experimental results. Wave absorption and effects of focusing and divergence of rays were taken into consideration in the radio wave modeling process. The following basic results were obtained: The signal amplitude increases by 20–30 dB 1–1.5 h before the substorm expansion phase onset. At the same time the signal azimuth deviates towards north of the great circle arc for the propagation path. Compared with quiet periods there are effects due to irregularities and gradients in the area of the polar edge of the main ionospheric trough on the passing signals. Propagation mechanisms also change during substorms. The growth of signal amplitude before the substorm can be physically explained by both a decrease of the F2-layer ionization and a growth of the F2-layer height that leads to a decrease of the signal field divergence and to a drop of the collision frequency. Ionospheric gradients are also important. This increase of signal level prior to a substorm could be used for forecasting of space weather disturbed conditions.